INNOVATIVE SOLUTIONS FOR DEVELOPING CADETS' SPEAKING COMPETENCE THROUGH THE USE OF INTERACTIVE METHODS IN TEACHING ENGLISH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article will analyze the cadets analyzed innovative solutions for the development of oral compensation through the use of interactive methods. In particular, the efficiency of the organization of training through the role, discussion, debate, multimedia media and digital platforms will be considered. The study cover the opportunities to form free and communication-oriented speech in cadurs through the integration of modern methodological approaches, technological means and motivational methods. The educational process also reveals practical aspects of creativity and independent thinking in the educational process.